Insight into the secondary imbibition rate of concrete and its relationship with curing time - Alderete, Natalia Mariel (2020)
Long‐term capillary imbibition in cementitious materials is relevant to describe their durable behaviour. After several weeks, when capillary rise is no longer progressing, a distinguished change in the slope (from the mass gain ‐ fourth root of time relation) is noticed. Primary and secondary imbibition rates (PIR and SIR, respectively) can be obtained from such behaviour. Contrary to the widely investigated PIR, usually defined as the capillary absorption rate, the SIR has been scarcely examined. To evaluate this unexplored process, we contrasted values of SIR and porosity. Moreover, using statistical inference we evaluated the evolution of the SIR of concrete mixes with different composition and curing age. This paper presents the effect of curing on the SIR and the relation between porosity changes and SIR. Despite the decrease in capillary and intrudable porosity, SIR increases with curing time having an opposite evolution than the PIR. Another interesting finding is this increase is irrespective of mix composition (including cement type, w/b ratio, aggregate amount, presence of SCMs). Results show that the PIR and SIR are influenced by different mechanisms with dissimilar correlations with porosity and curing time.